Survival comparison between radiofrequency ablation and surgical resection for patients with small hepatocellular carcinoma: A systematic review and meta-analysis - Xuan, Dongchun (Medicine (Baltimore), 2021)
OBJECTIVE: This study aimed to evaluate and compare the long-term therapeutic efficacy of radiofrequency ablation (RFA) versus that of surgical resection in small hepatocellular carcinoma (HCC). METHODS: Relevant articles in English from PubMed, EMBASE, and the Cochrane Library were retrieved. Pooled hazard ratios (HRs) were calculated to assess the prognostic value of RFA compared with that of surgical resection. RESULTS: A total of 19 studies involving 15,071 patients were included. The combined HRs (95% confidence interval [CI]) of RFA for recurrence/relapse-free survival (RFS) and overall survival (OS) were 1.55 (95% CI = 1.29-1.86, I(2) = 72.5%) and 1.61 (95% CI = 1.29-2.01, I(2) = 60.4%), respectively, compared with surgical resection. In subgroup analyses according to study design, both RFS and OS of the prospective subgroups showed statistical significance, and no statistical heterogeneity existed between studies. CONCLUSION: Our clinical data suggest that surgical resection offers better long-term oncologic outcomes than RFA.